Mitochondrial Dysfunction and Oxidative Stress in Liver Transplantation and Underlying Diseases: New Insights and Therapeutics. Issue 11 (21st October 2021) - Shi, Shaojun; Wang, Ling; van der Laan, Luc J.W.; Pan, Qiuwei; Verstegen, Monique M. A.
Abstract : Mitochondria are essential organelles for cellular energy and metabolism. Like with any organ, the liver highly depends on the function of these cellular powerhouses. Hepatotoxic insults often lead to an impairment of mitochondrial activity and an increase in oxidative stress, thereby compromising the metabolic and synthetic functions. Mitochondria play a critical role in ATP synthesis and the production or scavenging of free radicals. Mitochondria orchestrate many cellular signaling pathways involved in the regulation of cell death, metabolism, cell division, and progenitor cell differentiation. Mitochondrial dysfunction and oxidative stress are closely associated with ischemia-reperfusion injury during organ transplantation and with different liver diseases, including cholestasis, steatosis, viral hepatitis, and drug-induced liver injury. To develop novel mitochondria-targeting therapies or interventions, a better understanding of mitochondrial dysfunction and oxidative stress in hepatic pathogenesis is very much needed. Therapies targeting mitochondria impairment and oxidative imbalance in liver diseases have been extensively studied in preclinical and clinical research. In this review, we provide an overview of how oxidative stress and mitochondrial dysfunction affect liver diseases and liver transplantation. Furthermore, we summarize recent developments of antioxidant and mitochondria-targeted interventions.